2008
DOI: 10.1016/j.ejvs.2008.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Ischaemic Tissue Lesions after Infrainguinal Bypass Surgery for Critical Leg Ischaemia

Abstract: Complete healing of ischemic tissue lesions is slow even after a successful infrainguinal bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 21 publications
1
37
3
1
Order By: Relevance
“…The foot ulcer healing time reported in many studies varies widely depending on the patients' characteristics [30,31] and in particular were different for patients with neuropathic or ischaemic ulcers [16,32]. This is probably because in diabetic patients revascularisation can restore normal blood flow in the large vessels, including the pedal arteries, but cannot restore normal microvascular flow [33][34][35]. The fact that the post-revascularisation TcPO 2 in the Isc group was significantly higher than at baseline but remained significantly lower than the TcPO 2 in the Neu group confirms this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…The foot ulcer healing time reported in many studies varies widely depending on the patients' characteristics [30,31] and in particular were different for patients with neuropathic or ischaemic ulcers [16,32]. This is probably because in diabetic patients revascularisation can restore normal blood flow in the large vessels, including the pedal arteries, but cannot restore normal microvascular flow [33][34][35]. The fact that the post-revascularisation TcPO 2 in the Isc group was significantly higher than at baseline but remained significantly lower than the TcPO 2 in the Neu group confirms this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Patient loss to follow-up is common (13%-41%) in retrospective data and registry (17)(18)(19). In our small cohort, we managed to record complete data as we followed each patient at our outpatient clinic (multidisciplinary diabetic foot team) at least a year or until death.…”
Section: Discussionmentioning
confidence: 99%
“…the information regarding the probability of complete wound healing after surgical procedures in diabetic patients is limited (19). Hoffmann et al (22) systematically reviewed the literature and identified 1915 papers on revascularization in critical leg ischemia (cLI) with tissue lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease, tissue loss and coronary heart disease as well as impaired ambulatory status are predictors of poor outcome, especially after revascularization (26)(27)(28). Despite revascularization, ischaemic lesions have a tendency to heal slowly, especially in diabetics (29).…”
Section: The Problemmentioning
confidence: 99%